2010
DOI: 10.1038/eye.2010.73
|View full text |Cite
|
Sign up to set email alerts
|

A glaucoma equity profile: correlating disease distribution with service provision and uptake in a population in Northern England, UK

Abstract: Increasing access to services involves collaboration with optometrists, ophthalmologists, public health, and commissioners. It is no longer acceptable to rely on private high street optometry to provide primary eye care services in areas of high need. Outreach services must be developed and evaluated in areas of relative deprivation if world class eye services are to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 8 publications
1
33
1
Order By: Relevance
“…36,37,59,72,73 Older persons with visual impairment living in deprived areas are significantly less likely to take up eye examinations, suggesting an association between inequalities of older age and low SES. 37 Moreover, a study of solely female participants reported that women >65 years old and of manual social class were less likely to take up eye examinations in the UK.…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations
“…36,37,59,72,73 Older persons with visual impairment living in deprived areas are significantly less likely to take up eye examinations, suggesting an association between inequalities of older age and low SES. 37 Moreover, a study of solely female participants reported that women >65 years old and of manual social class were less likely to take up eye examinations in the UK.…”
Section: Agementioning
confidence: 99%
“…72 As noted previously with age-related inequalities, some ocular conditions are more prevalent in lower socioeconomic groups; namely, glaucoma and AMD. 60,73 Those from lower SES groups have been reported to present with glaucoma at significantly later stages than those of higher SES, 59,60 although Fraser et al 60 added that family history and time since last optometry visit also played a key role in this statistic. As mentioned previously, this places more deprived individuals at a significant disadvantage and at high risk of irreversible visual loss.…”
Section: Socioeconomicmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the commercially driven optometry model has resulted in a disparity of service provision where the socially deprived, who are known to present with more advanced disease or not at all, have the poorest access to optometry services. 5,6 Our disintegrated eye health service needs to identify ocular pathology at an earlier stage, for which targeted surveillance of the high risk may be advantageous over opportunistic screening. [7][8][9] This has already been successfully implemented in the NHS Diabetic Eye Screening Programme, 10 where the electronic transfer of patient information and imaging between community screening clinics and the Hospital Eye Service is now standard practice.…”
Section: Current Problemmentioning
confidence: 99%